Surf and Swash Zone Dynamics from High-Frequency Observations at a Microtidal Low-Energy Dissipative Beach - Dimitris Chatzistratis; Antonis E. Chatzipavlis; Isavela N. Monioudi; Adonis F. Velegrakis; Olympos P. Andreadis; Fotis Psarros; Ivan T. Petsimeris (Journal of Marine Science and Engineering)
This study examines the surf and swash zone dynamics of a microtidal, low-energy, dissipative beach in Kos Island, Greece, using high-frequency optical monitoring with a Beach Optical Monitoring System (BOMS) and in situ wave measurements during the winter period. Increased wave heights induced the offshore migration of the wave-breaking zone with significant alongshore variability; however, no triggering of NOM (Net Offshore Movement) behavior was verified, while occasional rhythmic patterns were observed in the breaking location under moderate wave conditions. Shoreline dynamics showed transient erosional episodes coupled with elevated run-up excursions, yet the shoreline showed signs of recovery, suggesting a quasi-equilibrium state. Run-up energy spectra were consistently dominated by lower frequencies than those of incoming waves under both low- and high-energy conditions. This behavior is attributed to the nearshore sandbars acting as low-pass filters, dissipating high-frequency wave energy and allowing for lower-frequency motions to dominate run-up processes. A widely used empirical wave run-up predictor corresponded well with the video observations, confirming its applicability to low-energy dissipative beaches. These results underscore the role of submerged sandbars in regulating wave energy dissipation and stabilizing beach morphology under low-to-moderate wave conditions.